NOTO´s internationalization strategy to Germany - Costa, Ana Sofia de Oliveira Pinho Dias da (2019)
The goal of this dissertation is to define an internalization strategy to NOTO- a small-medium furniture company- that pretends to expand its activity to foreign markets in order to increase its sales and consequently its economies of scale. Currently, the company produces, in outsourcing, premium furniture pieces in reduced quantities and their unit costs are quite high. NOTO´s intention is to increase its activity to start its internalization to a specific country- Germany. This dissertation presents a study of a possible strategy to enter the German market. Having in consideration the research performed and the company capabilities, exportation was considered the best approach to enter the market. Therefore, it was developed a strategy based on the Marketing 4Ps, where it is presented the way that NOTO can position itself on the German market in terms of: Product, Price, place and Promotion